J/Ψ-nuclear bound states - Tsushima, K.; Lu, D. H.; Krein, G. [UNESP]; Thomas, A. W. (American Physical Society (APS), 2011)
J/Ψ-nuclear bound state energies are calculated for a range of nuclei by solving the Proca (Klein-Gordon) equation. Critical input for the calculations, namely the medium-modified D and D* meson masses, as well as the nucleon density distributions in nuclei, are obtained from the quark-meson coupling model. The attractive potential originates from the D and D* meson loops in the J/Ψ self-energy in the nuclear medium. It appears that J/Ψ-nuclear bound states should produce a clear experimental signature provided that the J/Ψ meson is produced in recoilless kinematics. © 2011 American Physical Society.